Outpatient versus inpatient uterine polyp treatment for abnormal uterine bleeding: randomised controlled non-inferiority study. - Cooper, Natalie A.M.; Clark, T. Justin; Middleton, Lee; Diwakar, Lavanya; Smith, Paul; Denny, Elaine; Roberts, Tracy; Stobert, Lynda; Jowett, Susan; Daniels, Jane; Thornton, Jim (British Medical Association, 2015)
OBJECTIVE: To compare the effectiveness and acceptability of outpatient polypectomy with inpatient polypectomy. DESIGN: Pragmatic multicentre randomised controlled non-inferiority study. SETTING: Outpatient hysteroscopy clinics in 31 UK National Health Service hospitals. PARTICIPANTS: 507 women who attended as outpatients for diagnostic hysteroscopy because of abnormal uterine bleeding and were found to have uterine polyps. INTERVENTIONS: Participants were randomly assigned to either outpatient uterine polypectomy under local anaesthetic or inpatient uterine polypectomy under general anaesthesia. Data were collected on women's self reported bleeding symptoms at baseline and at 6, 12, and 24 months. Data were also collected on pain and acceptability of the procedure at the time of polypectomy. MAIN OUTCOME MEASURES: The primary outcome was successful treatment, determined by the women's assessment of bleeding at six months, with a prespecified non-inferiority margin of 25%. Secondary outcomes included generic (EQ-5D) and disease specific (menorrhagia multi-attribute scale) quality of life, and feasibility and acceptability of the procedure. RESULTS: 73% (166/228) of women in the outpatient group and 80% (168/211) in the inpatient group reported successful treatment at six months (intention to treat relative risk 0.91, 95% confidence interval 0.82 to 1.02; per protocol relative risk 0.92, 0.82 to 1.02). Failure to remove polyps was higher (19% v 7%; relative risk 2.5, 1.5 to 4.1) and acceptability of the procedure was lower (83% v 92%; 0.90, 0.84 to 0.97) in the outpatient group Quality of life did not differ significantly between the groups. Four uterine perforations, one of which necessitated bowel resection, all occurred in the inpatient group. CONCLUSIONS: Outpatient polypectomy was non-inferior to inpatient polypectomy. Failure to remove a uterine polyp was, however, more likely with outpatient polypectomy and acceptability of the procedure was slightly lower.